2023
DOI: 10.1007/s40948-023-00635-y
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis and deformation control method of swelling soft rock roadway adjacent to chambers

Abstract: The surrounding rock of swelling soft rock roadway has high clay mineral content, strong expansibility after encountering water, low strength and poor cementation. The roadway is prone to large deformation under the influence of complex geostress. Combined with the support change of the development roadway of 2# coal in Hongqingliang mine, through geological survey, field observation and indoor test, the failure mechanism of the traditional support method of “anchor bolt + anchor cable + anchor mesh + shotcret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…On the one hand, reinforced support of anchor cables can connect the deep surrounding rock with the pretightening force bearing structure formed by rock bolt support. This will fully mobilize the bearing capacity of deep surrounding rock and realize the common bearing capacity of rock mass in a wider range [46]. On the other hand, the high pretightening force provides surrounding rock with compressive stress, which played a part in forming a skeletal network structure with the compression stress area formed with rock bolts, keeping the overall stability of surrounding rock [47,48].…”
Section: Segmental Control Strategiesmentioning
confidence: 99%
“…On the one hand, reinforced support of anchor cables can connect the deep surrounding rock with the pretightening force bearing structure formed by rock bolt support. This will fully mobilize the bearing capacity of deep surrounding rock and realize the common bearing capacity of rock mass in a wider range [46]. On the other hand, the high pretightening force provides surrounding rock with compressive stress, which played a part in forming a skeletal network structure with the compression stress area formed with rock bolts, keeping the overall stability of surrounding rock [47,48].…”
Section: Segmental Control Strategiesmentioning
confidence: 99%
“…Te whole process from loading deformation to destruction of coal body is accompanied by the accumulation and transformation of energy. Energy is the essential factor leading to the destruction of the coal bodies [19][20][21][22][23][24][25][26]. Many scholars have carried out a lot of research on energy and rock failure, but there are few studies on the energy of cracked coal, which still needs further research.…”
Section: Introductionmentioning
confidence: 99%
“…At present, U-shaped steel shed is widely used in mining engineering, but there are obvious differences in economy, stiffness, bearing capacity and other aspects of U-shaped steel shed based on different support time [ 21 , 22 ]. Zhang et al [ 23 ] found that the U-shaped steel shed is difficult to be removed and repaired after the roadway is damaged and deformed. The construction and support time of the U-shaped steel shed would have a significant impact on the support effect.…”
Section: Introductionmentioning
confidence: 99%